Enhancement of isopropanol removal with concomitant power generation by microbial fuel cells: Optimization of deoxidizing composite anodes using response surface methodology. (January 2022) - Liu, Shu-Hui; Lin, Hsin-Hui
Abstract: This study used a response surface method to develop a deoxidizing anode, which was introduced into microbial fuel cells (MFCs) to treat isopropanol (IPA) wastewater and waste gas. By embedding a deoxidizing agent (DA) into the anode of MFCs, a hypoxic environment can be created to enable anaerobic electrogens to be effectively attached to the anode surface and grow. Consequently, MFC power generation performance can be enhanced. The optimal coke and conductive carbon black ratio of an anode and percentage of DA added were 3.61 g/g and 3.15 %, respectively. The research design concurrently achieved the maximum deoxygenation efficiency (0.86 mg O2 /bead), minimum disintegration ratio (3.51 %), and minimum resistance (30.2 Ω). The regression model had high prediction power (R 2 > 0.93) for anode performance. As determined through multi-objective optimization, the results highly satisfied the target expectation (desirability = 0.82). The optimized deoxidizing anode was filled into an air-cathode MFC, which had a higher IPA removal efficiency (1.15-fold) and voltage output (1.24-fold) than an MFC filled with coke. The results for the trickling-bed MFC filled with a deoxidizing anode revealed that when the inlet concentration was 0.74 g/m 3, the voltage output and power density were highest at 416.3 mV and 486.6 mW/m 3, respectively. The deoxidizing anode developed has the potential to increase the MFC voltage output and the pollutant removal. Graphical abstract: Image 1 Highlights: The response surface method was used to optimize anode materials. Multiple prediction models that can optimize anode performance were established. The deoxidizing anode effectively decreased oxygen in the anode tank. The microbial fuel cell with deoxidizing anode enhanced power generation.